Rule and equipment modification issues in World Taekwondo Federation (WTF) competition - Moenig, U. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2015)
Background: At the beginning of the new millennium, the WTF was entangled in a variety of high-level scandals involving its leadership. In addition, taekwondo matches were often considered too boring to watch for audiences, and the IOC demanded more transparency in taekwondo`s scoring process. As a result, the taekwondo stablishment feared for its continuing membership as an official discipline in the Olympic Games. Therefore, the WTF initiated a variety of far-reaching rule and equipment changes during the past decade. Aim: The aim of this study is to examine the results of the rule changes and equipment modifications introduced to the competition system of the WTF after the year 2000. Method: The methodology used included the analysis of documents. In addition, general observations and interviews played a role in the process of deduction and synthesis. Results and Conclusion: Presently, the desired outcomes of the rule changes and equipment modifications have not been entirely accomplished. While there have been various improvements in the overall competition system, several unintended and unanticipated consequences have arisen from recent modifications. Moreover, it seems that the single-minded focus by the WTF on keeping taekwondo`s Olympic membership status has not always been the best for the sport.